The Formation of the Efficient System of Ecological Enterprise - YASNOLOB, Ilona; GORB, Oleg; OPARA, Nadiia; SHEJKO, Serhii; PYSARENKO, Svitlana; MYKHAІLOVA, Olena; MOKIIENKO, Tetyana (Journal of Environmental Management and Tourism, 2019)
The necessity of using ecologically oriented approach in the process of production by developing and introducing the system of ecological management was investigated in the article. The general principles of its formation with the directions of actions and results were determined. 14 principles of efficient management of V.Ye. Deming for raising the efficiency of ecological management system were adapted with the aim of its constant improving, ensuring long-term developing of enterprise, and raising its competitiveness. The conducting of SWOT-analysis in the system of ecological management was suggested for determining the strategies of enterprise activities, further improving and raising the efficiency of this system. The model of forming the efficient system of enterprise ecological management was suggested. The improvement and efficiency of this system presupposes using general principles and those of efficiency, external environmental information, and SWOT-analysis. The international experience of inefficient ecological management, proving the expediency of using the system of enterprise ecological management, was shown.